The relationship between capital structure and profitability: evidence from Malaysia / Norfaiezah Mohamad - Mohamad, Norfaiezah (2016)
The dominant issue in finance and had been keep pounder among researchers is whether the profitability of the companies is affected by the leverage. Nowadays, financing activities become important in every company in Malaysia. This is due for the companies to running their investment activities and for the most importantly to meet their working capital requirement. The companies have to considered their leverage before decide to use the debt or equity for their financing activities. Therefore, the management of companies in handling capital structure is very important. It’s to avoid the company have a higher in leverage. The purpose of this study is to identify whether there is relationship between the capital structure and the profitability. In this paper, the capital structure will be measured through financial leverage and the profitability will be measure using the return on asset and return on equity. The finding shows that there is positive relationship and significant between the debt ratio, interest coverage ratio with the return on asset. There is also negative relationship and significant between debt equity ratio and return on asset. Other than that, in return on equity there are positive relationship and significant to debt equity ratio and interest coverage ratio. However, there are negative relationship and significant between debt ratio and return on equity.